2022
DOI: 10.3390/app12157800
|View full text |Cite
|
Sign up to set email alerts
|

Honey as an Adjuvant in the Treatment of COVID-19 Infection: A Review

Abstract: Since ancestor times, honey has been used to promote human health due to its medicinal, and nutritious properties, mainly due to bioactive compounds present, such as phenolic compounds. The emergence of COVID-19, caused by the SARS-CoV-2 virus, led to the pursuit of solutions for the treatment of symptoms and/or disease. Honey has proven to be effective against viral infections, principally due to its potential antioxidant and anti-inflammatory activities that attenuate oxidative damage induced by pathogens, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 139 publications
(125 reference statements)
0
5
0
1
Order By: Relevance
“…In a systematic review of in-silico and clinical studies, the in-silico studies presented propolis of having potentially anti-viral effect on SARS-CoV-2, yet, limited clinical evidence are available to show that propolis and honey could potentially improve COVID-19 symptoms and faster viral clearance [ 46 ]. Similarly, another review suggested honey as an adjuvant in the treatment of COVID-19 infection, stating its antiviral properties related to its antioxidant and anti-inflammatory attributes and urging more clinical trials in the future [ 47 ]. Supplemental vitamins C, vitamin D, and natural honey, according to a review, seem promising to alleviate symptoms and disease progression alongside conventional treatment of COVID-19, however, more extensive clinical validation is essential [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic review of in-silico and clinical studies, the in-silico studies presented propolis of having potentially anti-viral effect on SARS-CoV-2, yet, limited clinical evidence are available to show that propolis and honey could potentially improve COVID-19 symptoms and faster viral clearance [ 46 ]. Similarly, another review suggested honey as an adjuvant in the treatment of COVID-19 infection, stating its antiviral properties related to its antioxidant and anti-inflammatory attributes and urging more clinical trials in the future [ 47 ]. Supplemental vitamins C, vitamin D, and natural honey, according to a review, seem promising to alleviate symptoms and disease progression alongside conventional treatment of COVID-19, however, more extensive clinical validation is essential [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The benefits of these natural supplements stem from deeply rooted cultural norms, despite the fact that their impact on HRQoL during COVID-19 infection was not rigorously tested in the past. A previous clinical trial enlisted some of honey’s antiviral and antibacterial properties, since its antioxidant content hugely impacts the co-morbidities associated with SARS-CoV-2 infection [ 23 ]. However, our study findings cannot be conclusive, as experimental study designs are required.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of infectious diseases such as COVID-19, the experience might be different as other factors might play a role, such as previous vaccination (COVID-19, seasonal flu) and consumption of natural supplements such as drinking herbal drinks, consuming honey, or others which COVID-19 patients might perceive to be beneficial. Studies showed that herbal supplements and honey—which are commonly used in Saudi Arabia—have some antiviral activities [ 20 , 21 , 22 , 23 ]. In terms of vaccination, exploring the change in HRQoL during COVID-19 and after recovery can aid in persuading vaccine-hesitant groups to get vaccinated.…”
Section: Introductionmentioning
confidence: 99%
“…Salah satu produk yang dapat meningkatkan daya tahan tubuh yaitu madu. Penelitian terdahulu menyebutkan bahwa madu memiliki khasiat dalam melawan infeksi virus secara efektif, mampu melemahkan kerusakan oksidatif serta mampu meningkatkan sistem kekebalan tubuh (Soares et al, 2022). Fakta tersebut membuat produk ini digemari oleh masyarakat hingga membuat permintaan madu meningkat setiap harinya (Akhiroh et al, 2021).…”
Section: Pendahuluanunclassified